2018
DOI: 10.3390/nu10080956
|View full text |Cite
|
Sign up to set email alerts
|

A Synergistic Formulation of Plant Extracts Decreases Postprandial Glucose and Insulin Peaks: Results from Two Randomized, Controlled, Cross-Over Studies Using Real-World Meals

Abstract: This study investigated the efficacy of a plant-derived dietary supplement with respect to decreasing postprandial glucose and insulin peaks after the intake of real-world meals. Two randomized, double-blind, placebo-controlled, cross-over experiments were conducted on healthy subjects who received a supplement containing extracts of white mulberry, white bean, and green coffee or one containing the three extracts with added fibre before consuming high-GI/GL (glycaemic index/glycaemic load) meals. In study one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Another investigation revealed that phytochemicals from plants not only reduce the blood glucose level during diabetes but also improves the hematological parameters (Sudasinghe & Peiris, 2018). The antioxidant and anti-α-glucosidase potentials of H. lagenicaulis extracts were probably due to synergic behavior commonly observed with biologically functional plant extracts (Adamska-Patruno et al, 2018). The presence of high value bioactives in plants supports the efforts being made in search of safe and healthy therapeutic approaches for DMT-2 management.…”
Section: Discussionmentioning
confidence: 93%
“…Another investigation revealed that phytochemicals from plants not only reduce the blood glucose level during diabetes but also improves the hematological parameters (Sudasinghe & Peiris, 2018). The antioxidant and anti-α-glucosidase potentials of H. lagenicaulis extracts were probably due to synergic behavior commonly observed with biologically functional plant extracts (Adamska-Patruno et al, 2018). The presence of high value bioactives in plants supports the efforts being made in search of safe and healthy therapeutic approaches for DMT-2 management.…”
Section: Discussionmentioning
confidence: 93%
“…This could result in overeating and impaired insulin sensitivity. On the other hand, breakfast eating can aid in controlling appetite while also improving insulin sensitivity for the next meal (16,23). Furthermore, fasting from the previous night is interrupted by eating breakfast.…”
Section: Introductionmentioning
confidence: 99%
“…Another investigation revealed that phytochemicals from plants not only reduce the blood glucose level during diabetes but also improves the hematological parameters (Sudasinghe et al, 2018). The antioxidant and anti-α-glucosidase potentials of H. lagenicaulis extracts were probably due to synergic behavior commonly observed with biologically functional plant extracts (Adamska-Patruno, 2018). The presence of high value bioactives in plants supports the efforts being made in search of safe and healthy therapeutic approaches for DMT-2 management.…”
Section: Discussionmentioning
confidence: 87%